2005
DOI: 10.1086/428122
|View full text |Cite
|
Sign up to set email alerts
|

The Surprisingly Steep Mass Profile of A1689, from a Lensing Analysis of Subaru Images

Abstract: Subaru observations of A1689 (z = 0.183) are used to derive an accurate, model-independent mass profile for the entire cluster, r < ∼ 2Mpc/h, by combining magnification bias and distortion measurements. The projected mass profile steepens quickly with increasing radius, falling away to zero at r ∼ 1.0Mpc/h, well short of the anticipated virial radius. Our profile accurately matches onto the inner profile, r < ∼ 200kpc/h, derived from deep HST/ACS images. The combined ACS and Subaru information is well fitted b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
422
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(455 citation statements)
references
References 20 publications
28
422
5
Order By: Relevance
“…Kneib et al (2003) found c = 22 +9 −5 for the central mass concentration of the cluster Cl 0024 + 1654. Gavazzi (2005) concluded on c = 11.73 ± 0.55 for MS2137 − 23, while Broadhurst et al (2005) found c = 13.7 +1.4 −1.1 for Abell 1689. Limousin et al (2007) presented a thorough discussion of the different concentration parameters derived for Abell 1689 in the literature, concluding that a distribution of best fit c parameters is needed for observed lensing clusters in order to provide a sample large enough to make an adequate comparison with simulations.…”
Section: Best Fit Concentration Parametermentioning
confidence: 97%
“…Kneib et al (2003) found c = 22 +9 −5 for the central mass concentration of the cluster Cl 0024 + 1654. Gavazzi (2005) concluded on c = 11.73 ± 0.55 for MS2137 − 23, while Broadhurst et al (2005) found c = 13.7 +1.4 −1.1 for Abell 1689. Limousin et al (2007) presented a thorough discussion of the different concentration parameters derived for Abell 1689 in the literature, concluding that a distribution of best fit c parameters is needed for observed lensing clusters in order to provide a sample large enough to make an adequate comparison with simulations.…”
Section: Best Fit Concentration Parametermentioning
confidence: 97%
“…This is often referred to as a dilution effect, because the contaminants dilute the signal (Broadhurst et al 2005;Umetsu et al 2010;Okabe et al 2010aOkabe et al , 2013. The dominant source of contaminant galaxies is faint cluster members, the number density of which increases towards the cluster core.…”
Section: Selection Of Background Galaxiesmentioning
confidence: 99%
“…Broadhurst et al 2005;Limousin et al 2007). It is therefore of prime importance to make a secure selection of background galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…(7) has a soft core which is different from the NFW profile obtained by N-body simulation. Nevertheless, recent gravitational lensing data support the existence of soft cores in clusters, in contradiction to the NFW profile (Tyson et al 1998;Sand et al 2002;Broadhurst 2005). …”
Section: Neutrinos In Clustersmentioning
confidence: 92%